The multistory parking garage and Square Alfredo Issa - Antonio Soukef Júnior; Antonio Busnardo Filho; Helena Napoleon Degreas (Labor & Engenho (Online), 2020)
The article shows the government recurring practice of neglect the assets under its responsibility which are the subject to significant modifications, random transformations, most often not considering the permanence of assets and their property values, cultural and aesthetic principles. The discontinuity of administrations and the absence of continued public policies lead to immediate actions causing the loss of memory of emblematic places in cities. To illustrate this situation, we describe the transformation of the Square and the Alfredo Issa garage building, built-in downtown São Paulo in the early 1970s, through historical research into primary and secondary sources and on-site analysis.